STUDI PENGENDALIAN BANJIR DI KOTA BARABAI TERKAIT RENCANA PEMBANGUNAN BENDUNGAN PANCUR HANAU DI SUNGAI BARABAI KABUPATEN HULU SUNGAI TENGAH - Eddy Prabowo (Lambung Mangkurat University Press, 2018)
Major floods hit the Barabai city in June 2013, where this incident caused damage to the river border and floods inundated the city. Barabai River's rainfall and water level during the flood were recorded by the Baruh Batung's Automatic Water Level Recorder (AWLR) located in Hantakan Sub-District, Hulu Sungai Tengah Regency. In this case, the Hulu Sungai Tengah Regency Government plans to build the Hanau Pancur dam on the Barabai River so that it is expected to reduce flood discharge in the Barabai city. The calibration of flood drainage and discharge coefficients in June 2013 is indispensable in the design of the Hanau Pancur dam and the determination of water level as an early warning of flood hazards. The method used to determine the flow coefficient uses Dr. Kawakami equation. In calibration of flood discharges in the Barabai watershed using the method of hydraulic analysis and hydrological analysis. The method of determining the water level as an early warning of flood hazard uses flood tracking on the overflow. The result is the drainage coefficient in the 100 year return period of 0.895 and the equivalent flood discharge in June 2013 in the Barabai watershed of 605.64 m3 / sec. The height of the flood water above the Abundance of the Hanau Pancur dam as an early warning of flood hazard for the conditions of alert 1, standby 2 and standby 3 respectively 1.55 m, 1.65 m and 1.78 m. With the construction of the Hanau Pancur dam on the Barabai River, the reduction in flood discharge Q100, Q1000 and QPMF were respectively 11.70%, 11.19% and 9.75%.